Bivalent Histone Codes on WNT5A during Odontogenic Differentiation. (January 2018) - Zhou, Y.; Zheng, L.; Li, F.; Wan, M.; Fan, Y.; Zhou, X.; Du, W.; Pi, C.; Cui, D.; Zhang, B.; Sun, J.; Zhou, X.
Lineage-committed differentiation is an essential biological program during odontogenesis, which is tightly regulated by lineage-specific genes. Some of these genes are modified by colocalization of H3K4me3 and H3K27me3 marks at promoter regions in progenitors. These modifications, named "bivalent domains, " maintain genes in a poised state and then resolve for later activation or repression during differentiation. Wnt5a has been reported to promote odontogenic differentiation in dental mesenchyme. However, relatively little is known about the epigenetic modulations on Wnt5a activation during tooth development. Here, we investigated the spatiotemporal patterns of H3K4me3 and H3K27me3 marks in developing mouse molars. Associated H3K4me3 methylases (mixed-lineage leukemia [MLL] complex) and H3K27me3 demethylases (JMJD3 and UTX) were dynamically expressed between early and late bell stage of human tooth germs and in cultured human dental papilla cells (hDPCs) during odontogenic induction. Poised WNT5A gene was marked by bivalent domains containing repressive marks (H3K27me3) and active marks (H3K4me3) on promoters. The bivalent domains tended to resolve during inducted differentiation, with removal of the H3K27me3 mark in a JMJD3-dependent manner. When JMJD3 was knocked down in cultured hDPCs, odontogenic differentiation was suppressed. The depletion of JMJD3 epigenetically repressed WNT5A activation by increased H3K27me3 marks. In addition, JMJD3 could physically interact with ASH2L, a component of the MLL complex, to form a coactivator complex, cooperatively modulating H3K4me3 marks on WNT5A promoters. Overall, our study reveals that transcription activities of WNT5A were epigenetically regulated by the negotiated balance between H3K27me3 and H3K4me3 marks and tightly mediated by JMJD3 and MLL coactivator complex, ultimately modulating odontogenic commitment during dental mesenchymal cell differentiation.